Tinjauan Hukum Islam Pada Cerai Talak Terhadap Pernikahan dengan Mahar Tidak Tunai - Rizki Zul Akhiriah Hasibuan (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this research is to find out: (1) the legal consequences of talak divorce on marriages with non-cash dowry, (2) to find out the legal status of the husband's unpaid dowry debt after talak divorce. The type of research used in this research is qualitative research. In this qualitative method, research is carried out directly in the field or at the research location. The research approach used in this research is in the form of a library study (Library Research). Based on the results of the research and discussion in this study, it can be concluded that: For a husband who divorces his wife even though he has not had sexual relations with her, he only has the obligation to pay half of the dowry amount that has been determined before the marriage contract is carried out. However, a husband who has had sex with his wife and then divorces or des not divorce, still has the obligation to pay all the dowry that has been determined by the prospective husband. Meanwhile, for a husband who dies, according to the opinion of most Islamic law experts, it is still obligatory to pay the specified dowry even though during his lifetime he never had sexual intercourse with her (dukhul). Paying debts in Islam is obligatory and you cannot delay paying off all your debts. Likewise, the dowry law must be paid by the prospective husband to the prospective wife at the time of the marriage contract, but if the dowry is postponed then it is still permissible as long as the time for repayment is clear. Paying dowry debts according to the Compilation of Islamic Law is permissible to be owed and may also be deferred if the bride-to-be is happy and gives permission if the dowry is deferred. In this case, the dowry is still owed in the event of separation (divorce), a husband's obligation is to pay the dowry from the assets owned by a husband during the marriage and the dowry owed can be settled after the divorce occurs.